Metadiscourse in csr reports of mass media giants: Walt Disney and Comcast Corporation - Mahathir, Nurul Fatihah; Abdul Aziz, Roslina (GADING Journal for the Social Sciences, 2024)
The disclosure of information regarding how organisations fulfil their social responsibilities has gained significance and become a common phenomenon during the last few decades. This development necessitates the use of Corporate Social Responsibility (CSR) reporting as it is recognised as strategic tools for communication with stakeholders. Corporate leaders strategically incorporate metadiscourse resources in CSR reports to establish connections with readers, indicating a link between metadiscourse use and CSR reporting. The study aimed at determining the types and frequency of interactive and interactional metadiscourse resources in Walt Disney’s and Comcast Corporation’s CSR reports and they key metadiscourse devices and their functions in the reports. A corpus-based approach was adopted in analysing the data. A specialised corpus consisting of CSR reports from Walt Disney and Comcast Corporation with the tokens of 26624 was used as the corpus data. Hyland’s Interpersonal Model of Metadiscourse was adopted as the analysis parameters. The findings revealed that both companies strategically focused on transitions, particularly ‘and’ and self-mentions ‘our,' 'we,' and company’s names. The study concludes that the frequent use of transitions, aids readability and guides comprehension, while the prevalence of self-mentions indicates collective ownership, active involvement in CSR initiatives, and a strong commitment to accountability. The study has implications for ESP and EAP education, as findings can be used to aid in designing and developing effective communication skills in professional settings.